2023
DOI: 10.1177/09636897231163217
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapies for Autism Spectrum Disorder Based on New Pathophysiology: A Review

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by difficulties in social communication, repetitive behaviors, and restricted interests, with onset early in life. The prevalence of ASD has increased worldwide in the last two decades. However, there is currently no effective therapy for ASD. Therefore, it is important to develop new strategies for ASD treatment. Evidence for the relationship between ASD and neuroinflammation, ASD and microglia, and ASD and glucose metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…While literature supporting the effectiveness of stem cells, and in particular of NPCs, for neurodegenerative disorders is wide (Lindvall and Kokaia, 2010), only few evidence are available regarding their application for neurodevelopmental diseases (NDDs) (Siniscalco et al, 2018; Donegan and Lodge, 2020). Most of these studies investigated the therapeutic efficacy of mesenchymal or hematopoietic stem cells on animal models of autism spectrum disorders (ASD) and in a limited number of cases amniotic epithelial or adipose- and urine-derived stem cells were used (Nabetani et al, 2023). Concerning RTT, the ability of mesenchymal stem cells to increase neurogenesis and the number of synapses in the brain of Mecp2 KO mice was recently reported; however, stem cells were engineered to constantly produce BDNF, becoming a supplier system for the neurotrophin (Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While literature supporting the effectiveness of stem cells, and in particular of NPCs, for neurodegenerative disorders is wide (Lindvall and Kokaia, 2010), only few evidence are available regarding their application for neurodevelopmental diseases (NDDs) (Siniscalco et al, 2018; Donegan and Lodge, 2020). Most of these studies investigated the therapeutic efficacy of mesenchymal or hematopoietic stem cells on animal models of autism spectrum disorders (ASD) and in a limited number of cases amniotic epithelial or adipose- and urine-derived stem cells were used (Nabetani et al, 2023). Concerning RTT, the ability of mesenchymal stem cells to increase neurogenesis and the number of synapses in the brain of Mecp2 KO mice was recently reported; however, stem cells were engineered to constantly produce BDNF, becoming a supplier system for the neurotrophin (Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other stem cells, such as mesenchymal cells, were widely used with therapeutic purposes in the field of neurodevelopmental and neurocognitive disorders, and a clinical trial on a small group of RTT patients treated with NPCs was reported on a Chinese journal (Liu et al, 2013; Nabetani et al, 2023). However, to the best of our knowledge, no study reports exhaustive results supporting the efficacy of NPCs in RTT.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ]. Finally, the increased NSE and neuronal destruction in ASD is an additional argument for cellular therapies, which, in some cases, can replace the affected neurons in the deficient neuronal networks and be able to function because of the different temporal circumstances [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…They noticed that all stem cell types have the universal abilities of homing and mobility. The current subtypes of stem cells under study for ASD links include fetal stem cells (FSC), mesenchymal stem cells (MSC) [ 190 ], hematopoietic stem cells (HSC), and umbilical cord [ 191 ]. One subtype is considered the cutting-edge variant in stem cell therapy and is called induced pluripotent stem cells (iPSC).…”
Section: A Brief Look At Cellular Therapiesmentioning
confidence: 99%